Toxicity assessment of arsenic and cobalt in the presence of aquatic humic substances of different molecular sizes - Watanabe, Cláudia Hitomi [UNESP]; Monteiro, Adnivia Santos Costa [UNESP]; Gontijo, Erik Sartori Jeunon [UNESP]; Lira, Vivian Silva [UNESP]; Bueno, Carolina de Castro [UNESP]; Kumar, Nirmal Tej [UNESP]; Fracácio, Renata [UNESP]; Rosa, André Henrique [UNESP] (Elsevier, 2017)
The release of contaminants in aquatic ecosystems can be influenced by humic acids. In this study, toxicity tests using environmentally relevant concentrations of arsenic and cobalt were conducted both in the presence and absence of aquatic humic substances (AHS) and the fractions of different molecular sizes in the range of (<5, 5–10;10–30; 30–100 and >100 kDa) using the microcrustacean Ceriodaphnia dubia. AHS together with arsenic reduced the toxicity, and the toxicity decreased in fractions of larger molecular size AHS. Despite the presence of cobalt, the reduction in toxicity was not observed and that depended on the molecular size of AHS. There was a trend of enhanced toxicity for Co in fractions of larger molecular sizes, opposed to that found for arsenic. Thus, the humic substances alter toxicity of trace elements, and this effect varies depending on the size of the humic substances
Keywords: Arsenic; C. dubia; Cobalt; Humic substances; Molecular size; Toxicity